Responding to Trends in Digital-Based Classroom Learning: Efforts to Improve Learning Outcomes of Indonesian Millennial Students at Bengkulu University - Baryanto Baryanto; Darmawanta Sembiring; B.M.A.S. Anaconda Bangkara; Khasanah Khasanah; Aunurrahman Aunurrahman (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
Through interviews with several academic activities and campus management at the University of Bengkulu, we have managed to obtain several data which are also backed up by secondary data from the publications we reviewed to answer the study themes which aim to respond to digital-based learning trends in efforts to improve millennial student learning outcomes. The author understands that the trend of using digital in learning is familiar. However, to gain new knowledge, we try to get direct data through conversations with staff and decision-making at the University of Bengkulu. We can analyze the results of both the interview data and the review of various sources under a phenomenological approach, in which, among other things, we coded data and revised the data to interpret the data. The latest data contains elements of validity and reliability that can be relied upon. Based on the study's results and available data, the University of Bengkulu believes that digital-based learning is a practical, transformative, and productive solution to improving the learning outcomes of Indonesian students who are said to be millennials. These findings will provide new insights into future discussions of similar studies.  Keywords: Digital Base Classroom, Improving Learning Outcome, Digital Classrom Learning